1366Environmental noise exposure and mental health: an analysis of a longitudinal survey of Australian households. (2nd September 2021) - Li, Ang; Mansour, Adelle; Martino, Erika; Bentley, Rebecca
Abstract: Background: Persistent exposure to environmental noise in people's homes has been associated with cardiovascular disease and poor mental health. Many studies conducted on noise and health are based on observational studies and the extent to which findings reflect residual confounding are not known. Methods: Using the Household, Income and Labour Dynamics survey in Australia, we examine the impact of environmental noise (traffic, airplanes, train, industry) on self-reported mental health measured by the Short Form 36 Health Survey. Fixed-effects longitudinal regression analyses are used to account for differences between people over time, reducing confounding from time-invariant factors and reporting bias. Time-varying factors were adjusted including age, education, equivalised income, employment, household structure, chronic condition, government payment status and tenure type. Results: Results show a significant decrease in average mental health as the level of noise increased. Exposure to loud traffic noise 'fairly commonly' or 'very commonly' negatively impacted mental health (-1.18; 95%CI -1.56, -0.81 and -1.33; 95%CI -1.77, -0.89) and exposure to noise from airplanes, trains or industry 'fairly commonly' or 'very commonly' negatively impacted mental health (-1.57; 95%CI -1.88, -1.27 and -1.48; 95%CI -1.89, -1.08). Conclusions: This provides robust evidence of short-run mental health effects of noise exposure within people's homes. More research could be done to explore this over a longer-time frame. Key messages: With increasing numbers of people living in urban areas, reducing environmental noise near people's homes or improving the capacity of homes to reduce external sources of noise (e.g. double glazing) may have public health benefit.